2019
DOI: 10.3390/md17060363
|View full text |Cite
|
Sign up to set email alerts
|

Oncolytic Vaccinia Virus Expressing Aphrocallistes vastus Lectin as a Cancer Therapeutic Agent

Abstract: Lectins display a variety of biological functions including insecticidal, antimicrobial, as well as antitumor activities. In this report, a gene encoding Aphrocallistes vastus lectin (AVL), a C-type lectin, was inserted into an oncolytic vaccinia virus vector (oncoVV) to form a recombinant virus oncoVV-AVL, which showed significant in vitro antiproliferative activity in a variety of cancer cell lines. Further investigations revealed that oncoVV-AVL replicated faster than oncoVV significantly in cancer cells. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 49 publications
2
22
0
Order By: Relevance
“…A large number of studies have shown vaccinia virus to be well suited to biological cancer therapies. [29][30][31] It is worth noting that the combination of the oncolytic virus and Recent studies have shown MDA-7/IL-24 to control many mi-croRNAs, such as miR-221, which is upregulated in many types of cancer. 33 MDA-7/IL-24 downregulated miR-221, which in turn induces Beclin-1, leading to autophagy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A large number of studies have shown vaccinia virus to be well suited to biological cancer therapies. [29][30][31] It is worth noting that the combination of the oncolytic virus and Recent studies have shown MDA-7/IL-24 to control many mi-croRNAs, such as miR-221, which is upregulated in many types of cancer. 33 MDA-7/IL-24 downregulated miR-221, which in turn induces Beclin-1, leading to autophagy.…”
Section: Discussionmentioning
confidence: 99%
“…34,35 In our study, luteolin can increase VV-mediated IL-24 gene expression in liver cancer cells in vitro and in vivo. The ERK signaling pathway is necessary for the replication of vaccinia virus, 29 and whether luteolin promotes the expression of IL-24 through the ERK signaling pathway needs to be further explored. Furthermore, F I G U R E 4 VV-IL-24 and luteolin synergistically inhibit MHCC97-H cell growth in a mouse xenograft model.…”
Section: Discussionmentioning
confidence: 99%
“…OncoVV-AVL was tested also on Balb/c nude mice bearing BEL-7404-or HCT116-derived tumors. In both cases, oncoVV-AVL efficiently inhibited tumor growth [63] (Table 2).…”
Section: Phylum Poriferamentioning
confidence: 91%
“…In vivo experiments showed that oncoVV-AVL induces a significant antitumor effect in colorectal cancer and liver cancer mouse models. These findings open the possibility of using the virus, containing marine lectin AVL, in oncolytic viral therapies [9].…”
mentioning
confidence: 87%
“…One article discusses the fatty acid composition and thermotropic behavior of glycolipids and other membrane lipids of green macrophyte Ulva lactuca [7]. Three articles cover lectin subjects [8][9][10]. One review article analyzes the results and perspectives of marine and freshwater lectins' application in experimental oncology and the therapy of oncological diseases; another article describes the use of a sponge lectin in the construction of a recombinant virus.…”
mentioning
confidence: 99%